2006
DOI: 10.1227/01.neu.0000199159.32210.e4
|View full text |Cite
|
Sign up to set email alerts
|

Stent-assisted Intracranial Recanalization for Acute Stroke: Early Results

Abstract: Stent-assisted recanalization for acute stroke resulting from intracranial thrombotic occlusion is associated with a high recanalization rate and low intracranial hemorrhage rate. These initial results suggest that stenting may be an option for recalcitrant cerebral arterial occlusions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
110
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 144 publications
(112 citation statements)
references
References 13 publications
1
110
0
1
Order By: Relevance
“…[2][3][4][5] Several authors have reported that intracranial stents could be used for AIS management with high recanalization and low complication rates. [6][7][8][9][10] Levy et al 7 reported 19 cases of intracranial stent placement for recanalizing vessels that were resistant to standard thrombolytic techniques, demonstrating a 79% recanalization rate of TIMI/TICI 2 or 3 with balloonmounted stents. One year later, Levy et al 8 also reported 18 cases of self-expandable stents for recanalization of acute cerebrovascular occlusion, demonstrating a 79% recanalization rate of TIMI/TICI 2 or 3 with Neuroform 3 and Wingspan stents (Boston Scientific/Target).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…[2][3][4][5] Several authors have reported that intracranial stents could be used for AIS management with high recanalization and low complication rates. [6][7][8][9][10] Levy et al 7 reported 19 cases of intracranial stent placement for recanalizing vessels that were resistant to standard thrombolytic techniques, demonstrating a 79% recanalization rate of TIMI/TICI 2 or 3 with balloonmounted stents. One year later, Levy et al 8 also reported 18 cases of self-expandable stents for recanalization of acute cerebrovascular occlusion, demonstrating a 79% recanalization rate of TIMI/TICI 2 or 3 with Neuroform 3 and Wingspan stents (Boston Scientific/Target).…”
Section: Discussionmentioning
confidence: 99%
“…[3][4][5][6][7][8][9][10]15 We assume that the high rate of dissection might be caused by relatively old age, vessel tortuosity, the previously existing vascular stenosis, and the emergent procedures with narrow time windows. In addition, all dissections were related to manipulation of balloonmounted stents, not to self-expandable stents.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The largest and most current study retrospectively analyzed 19 patients with acute stroke who underwent intracranial stent placement after failure of pharmacological and/or mechanical thrombolysis. 19 All patients had an NIHSS score > 16 with 8 occlusions in the ICA terminus, 7 in the MCA, and 4 in the basilar artery. The overall recanalization rate was 79% with only 1 asymptomatic ICH.…”
Section: Angioplasty and Stent Placementmentioning
confidence: 99%